POLA KONSUMSI MASYARAKAT MISKIN DI DESA TIWOHO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Kristin N. Tamawiwi; Theodora R. Katiandagho; Leonardus R. Rengkung; Tommy F. Lolowang (Universitas Sam Ratulangi, 2015)
ABSTRAK The purpose of this study is to analyze the consumption patterns of poor people in the village of Tiwoho.The data used in this study is primary data and secondary data. The primary data obtained by directly asking to the respondents based on a list of questionnaire in the village of Tiwoho, whereas secondary data is taken from the Central Bureau of Statistics. The determination of the location is done by using purposive sampling in the village of Tiwoho consits ofÂ 301 poor households as population taken 27 households as the reperesentative sample.The results showed that the higher the number of dependents, the expenditure on consumption will also increase, and the higher the level of education, the patterns of consumption will be higher as well. The consumption patterns of poor people who live in the village Tiwoho Wori District of North Minahasa Regency is divided into two categories, namely food and non-food consumption. The largest consumption patterns is on food consumption because of the influence of population income. Â Keywords: Consumption pattern, Poor People